A new species of the oligotrophic genus ochroconis (Sympoventuriaceae) - Samerpitak, K.; Duarte, A. P. M. [UNESP]; Attili-Angelis, D.; Pagnocca, Fernando Carlos [UNESP]; Heinrichs, G.; Rijs, A. J. M. M.; Alfjorden, A.; van den Ende, A. H. G. Gerrits; Menken, S. B. J.; Hoog, G. S. de [UNESP] (Springer, 2015)
Ochroconis globalis, a novel species of the melanized genus Ochroconis (Sympoventuriaceae, Venturiales), is described and illustrated and distinguished phenotypically and molecularly from existing ochroconis-like species. Phylogenetic analyses using nuclear ribosomal DNA genes (nuSSU, ITS, nuLSU) and coding gene fragments (ACT1, BT2, TEF1) revealed clustering of all strains as a monophyletic clade which was well separated from known Ochroconis species. Most strains of the new species were obtained from human-made environments, while the natural habitat of the species remains enigmatic. The new combination Ochroconis musae is introduced for one of the most commonly encountered Ochroconis species, and a phenotypic key to all species is provided.
Keywords: Ochroconis; Ant fungus; Opportunist; Phylogeny; Venturiales